Deep Learning for Whole Slide Image Analysis: An Overview - Dimitriou, Neofytos; Arandjelović, Ognjen; Caie, Peter D. (Frontiers in Medicine, 2019)
The widespread adoption of whole slide imaging has increased the demand for effective and efficient gigapixel analysis. Deep learning is at the forefront of computer vision, showcasing significant improvements over previous methodologies on visual understanding. However, whole slide images have billions of pixels and suffer from high morphological heterogeneity as well as from different types of artefacts. Collectively, these impede the conventional use of deep learning. For the clinical translation of deep learning solutions to become a reality, these challenges need to be addressed. In this paper, we review work on the interdisciplinary attempt of training deep neural networks using whole slide images, and highlight the different ideas underlying these methodologies.